2015
DOI: 10.5194/bg-12-6279-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of prescribed burning on soil greenhouse gas fluxes in a suburban native forest of south-eastern Queensland, Australia

Abstract: Abstract. Prescribed burning is a forest management practice that is widely used in Australia to reduce the risk of damaging wildfires. Prescribed burning can affect both carbon (C) and nitrogen (N) cycling in the forest and thereby influence the soil-atmosphere exchange of major greenhouse gases, i.e. carbon dioxide (CO 2 ), methane (CH 4 ) and nitrous oxide (N 2 O). To quantify the impact of a prescribed burning (conducted on 27 May 2014) on greenhouse gas exchange and the potential controlling mechanisms, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Some authors report unaltered pH values and ephemeral variations in electrical conductivity (Badía et al 2017;Alcañiz et al 2020), while, one year after the prescribed fire, other research shows marked decreases in nitrogen (Blankenship and Arthur 1999;Muqaddas et al 2015) as well as the recovery to pre-fire contents of magnesium and calcium (Alcañiz et al 2020). It has been found that the recovery of pre-fire soil properties may take place over short (Zhao et al 2015) or long (Alcañiz et al 2016) time spans, depending on fire temperature and residence time, topography of the burned area, rainfall, and degree of vegetation regeneration (Úbeda et al 2018;Girona-García et al 2019). Therefore, further research is needed to better understand the effects of prescribed fires in environments with contrasting characteristics (Hubbert et al 2006;Hueso-González et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors report unaltered pH values and ephemeral variations in electrical conductivity (Badía et al 2017;Alcañiz et al 2020), while, one year after the prescribed fire, other research shows marked decreases in nitrogen (Blankenship and Arthur 1999;Muqaddas et al 2015) as well as the recovery to pre-fire contents of magnesium and calcium (Alcañiz et al 2020). It has been found that the recovery of pre-fire soil properties may take place over short (Zhao et al 2015) or long (Alcañiz et al 2016) time spans, depending on fire temperature and residence time, topography of the burned area, rainfall, and degree of vegetation regeneration (Úbeda et al 2018;Girona-García et al 2019). Therefore, further research is needed to better understand the effects of prescribed fires in environments with contrasting characteristics (Hubbert et al 2006;Hueso-González et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although fire may have a positive influence on the soil, divergent conclusions have been reported (Neff et al 2005;Verma and Jayakumar 2012;Heydari et al 2015), suggesting that the question of how fire affects soils and plant growth has not been answered. Fire has decreased soil nutrients through volatilization (Zhao et al 2015). Inbar et al (2014) reported a significant decrease of organic matter in the soil following a severe fire, which adversely affected chemical, physical and microbiological properties (Antoine et al 2013;Zhao et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Fire has decreased soil nutrients through volatilization (Zhao et al 2015). Inbar et al (2014) reported a significant decrease of organic matter in the soil following a severe fire, which adversely affected chemical, physical and microbiological properties (Antoine et al 2013;Zhao et al 2015). Decreases in soil organic N and C have also been observed after fire (Murphy et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Secondarily, the destruction of forest trees, shrubs and grasses will also have an effect of the food sources for the soil microbes. These effects will alter respiration from the soils for potentially years or decades after a wildfire [10][11][12].…”
Section: Introductionmentioning
confidence: 99%